Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan - Salman Farisi; Juli Irnawati; Muhammad Fahmi (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2020)
To achieve company goals, human resource management which has the potential to affect the performance of employees which will ultimately affect the performance of the company. To be able to show the performance of the employees PT. Perkebunan Nusantara V (Persero) Kebun Tanah Putih at Riau Province, the company is required to uphold the motivation and work discipline of the employees. The purpose of this study was to determine and analyze the influence of motivation and work discipline on the performance of employees of PT. Perkebunan Nusantara V (Persero)  Kebun Tanah Putih Provinsi Riau. The population in this study were all employees of PT. Perkebunan Nusantara V (Persero)  Kebun Tanah Putih at Riau Province, amounting to 162 people. While the sample in this study was 62 employees distributed in each section. Data analysis techniques using multiple linear regression. The results showed that simultaneously motivation and work discipline variables had a positive and not significant effect on the performance of employees of PT. Perkebunan Nusantara V (Persero) Kebun Tanah Putih at Riau Province. Based on the partial test it is known that motivation has a positive and significant effect on the performance of employees of PT. Perkebunan Nusantara V (Persero) Kebun Tanah Putih Riau Province, while work discipline has a positive and not significant effect on the performance of the employees of PT. Perkebunan Nusantara V (Persero) Kebun Tanah Putih at Riau Province.